Remediation of arsenic-contaminated soils and washing effluents - Jang, Min; Jung, S.H.; Sang, I.C.; Jae, K.P. (Elsevier, 2005)
Laboratory experiments were conducted to determine the distribution of various arsenic species in tailings and soils. Other specific goal of the tests were to evaluate the extraction efficiency of arsenic using alkaline or acid washing, to determine optimum operational parameters of alkaline washing, and to evaluate the arsenic precipitation of washing effluents by pH adjustment or ferric chloride addition. Alkaline washing using sodium hydroxide was found to be favorable in removing arsenic from tailings or soils having a higher portion of arsenic in the operationally defined crystalline mineral fraction of crystalline oxide and amorphous aluminosilicates. This is due to the ligand displacement reaction of hydroxyl ions with arsenic species and high pH conditions that can prevent readsorption of arsenic because predominant negatively charged crystalline oxides do not attract the negatively charged oxyanions. For tailings, sodium hydroxide had 10-20 times higher extraction efficiencies than hydrochloric- or citric acid. The optimum concentration of sodium hydroxide for soil washing was determined to be 200 mM for all samples, while the optimum ratios were 10:1 and 5:1 for tailings and field/river sedimentary soils, respectively. The washing effluent of river soil was effectively treated by adjusting pH to 5-6 with hydrochloric acid, resulting in arsenic concentrations of <50 Î¼g l-1. In the case of field soil effluent, an addition of ferric chloride with a minimum mass ratio of 11 (Fe/As) was needed to reduce the arsenic below 50 Î¼g l-1. Â© 2005 Elsevier Ltd. All rights reserved.